Effects of an eight-week pedal technique training program on functional threshold power and lower-extremity isokinetic strength in young cyclists - Kaplan, A. B.; Göksu, Ö.; Berisha, M. (Frontiers in Sports and Active Living, 2026)
Introduction: This study investigated the effects of an eight-week pedal technique training program on functional threshold power (FTP), knee isokinetic strength, and bilateral strength symmetry in young cyclists.